Різноманітність септальних нектарників Однодольних - Фіщук, Оксана; Fischuk, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2017)
Досліджено питання різноманітності септальних нектарників в Однодольних та ступінь їх вивченості для з’ясування можливості використання цих ознак у систематиці. Септальні нектарники наявні лише в Одно- дольних і, ймовірно, являють собою ключову інновацію цієї групи. The septalnectariesin Monocots and degree of scrutiny to determine the possibility of using these features in systematics were studied. Septalnectaries available only in Monocotsand probably represent a key innovation of this group. The structure of monocotsseptalnectariesis the subject of active discussion. There are several classifications of septalnectaries. According to the descriptive morphological classification, septalnectariy is an independent histological structure. Septalnectaries classified into three groups according E. Daumanom features: the features secretion, secretory epidermis by histology and by placing the nectaries body and output channel. Also septalnectaries are divided into the following types: external (longitudinal nectarial grooves that are on the outer surface of the ovary) and internal (concluded).
The Variety of Septalnectariesin Monocots
Keywords: Однодольні; нектар; зав’язь; септальний нектарник; гінецей; Monocots; nectar; ovary; gynoecium; septalnectaries